COPPER AND ZINC ACCUMULATION IN SEDIMENT AT STRAITS OF JOHOR (Malaysian Journal of Civil Engineering, 2018)
A study was carried out to investigate heavy metal level in aquatic environment and its effect due to land use. The main objective of this study is to evaluate the concentration of copper (Cu) and zinc (Zn) in sediment at Straits of Johor. Four sampling stations in Kampung Pasir Puteh were chosen for sediment sampling. Heavy metal analysis was carried out for zinc (Zn) and copper (Cu) using Atomic Absorption Spectrophotometer (AAS). The in-situ results showed dissolved oxygen concentration in the range of 0.31 to 5.90mg/L while pH was recorded at 7.35 to 8.29. Heavy metals analysis in sediment for copper depicts copper accumulation in sediments exceeded the allowable limit at Station 5 whereby the highest readings recorded was 146 Âµg/g. Zinc accumulation at Station 3, Station 4 and Station 5 exceeded the allowable limit which was 271 Âµg/g. Enforcement should be taken to reduce the accumulation of pollutants thus can prevent the aquatic environment from polluted.